Community Preparedness in Facing of Smog Disaster in Taraibangun Village, Mining District, Kampar Regency, Riau Province - Ramadhan, Fikri; Muzani; Setiawan, Cahyadi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2022)
Abstract This research aims to find out the level of community preparedness in Taraibangun Village in the face of smog disaster. This research was conducted in Taraibangun Village for 5 months from March-July 2020. The research method used is to use descriptive methods with survey approach, as well as data collection techniques by conducting observations and dissemination questionnaires to 100 respondents in 4 hamlets in Taraibangun Village. The result of this study is that in Taraibangun Village fell into the category almost ready with an overall score score of 62.45 for preparedness of hamlet 1 Taraibangun village entered the ready category with an overall score of 65.6, for the villagers 2 entered the category ready with an overall score of 65.9, for the community of hamlet 3 entered into the category of Almost Ready with an overall score of 57.45 and the last for hamlet 4 entered into the category of Almost Ready with an overall score of 60.21. The parameters of knowledge and attitude for all hamlets have good knowledge in understanding smog disasters, emergency response plans look low results, this is because many people are vulnerable to disasters but do not have a plan, the mobility of taraibangun village resources is also equally low because the mobility of resources in the community because the village government has never conducted preparedness training for the villagers. Keywords: Preparedness,Smog, Taraibangun Village